(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
This study aimed to evaluate soil degradation in specific farmlands near Zaria, Kaduna State, Nigeria. Data collection methods included conducting field surveys and analyzing soil samples in the laboratory for physico-chemical parameters. Soil samples were collected at a depth of 0-15 cm from five different farmlands in four wards of Zaria, resulting in a total of twenty samples. The samples were analyzed using Atomic Absorption Spectrophotometry to evaluate their physical and chemical properties. Principal Component Analysis and Pearson correlation were used for statistical analysis. Component 1 explains 30.8% of soil degradation, component 2 explains 25.6%, component 3 explains 14.5%, and component 4 explains 11.4%, totaling 82.2% of the variance explained by these four components. A factor loading greater than 0.75 is chosen as the parameter that most impacts land degradation in this study. Thus, in PC1, parameters of Bulk density (0.963), Porosity (-0.954), GMC (-0.287), Organic carbon (-0.77) and CEC (0.29) have strong effects on land degradation. PC2 explains CEC (0.753), Na (-0.513) and K (-0.88) to have effect on land degradation. PC3 explains parameters of Organic carbon (0.391), CEC (-0.221) and Na (0.205) to have strong impact on land degradation. While Organic carbon (0.822), CEC (0.395), Na (-0.178) and K (-0.149) have strong impacts on land degradation in PC4. The study indicates most soils of the study area were degraded. The study recommends that knowledge on the use of fertilizers to be effectively communicated to farmers in order to caution excess use and avoid future occurrence of soil degradation.